Comparative Studies Of The Antibacterial Activities Of The Extracts Of Parts Of The African Locust Bean (Parkia Biglobosa) Tree Against Hyper Beta Lactamase Producing Staphylococci (Phenotypic MRSA) Isolates From Orthopaedic Patients - OBAJULUWA, A. F; UDOBI, C. E; ONAOLAPO, J.A; OYI, A. R (International Journal of Pharma and Bio Sciences, 2010)
The antibacterial effect of the methanolic extracts of the leaves, stem bark and root of the African Locust Bean tree (Parkia biglobosa) against methicillin resistant Staphylococcus aureus (MRSA) isolated from the wounds, skins and beds of orthopaedic patients was studied and compared. This was with the intention of developing an alternative source of antibacterial agent that can be used against these resistant organisms from this plant. A total of 33, 36 and 48 isolates of hyper beta lactamase producing Staphylococci ( MRSA) from wounds, skin and beds of these patients were subjected to antibacterial activity test using the agar diffusion method. Results obtained showed that the crude methanolic extracts of the stem bark of Parkia biglobosa has the best activity followed by the roots and the leaves with these activity being concentration dependent. These results show that if the active constituents in the stem bark of Parkia biglobosa are identified, they can be compounded into a compatible dosage form that may serve as an alternative therapy for infections due to MRSA.